Pemilihan Supplier Menggunakan Metode Grey Based Rough Set dan Analisis Sensitivitas Kriteria Lingkungan - Ichda Rachmawati Putri; Aries Susanty (Industrial Engineering Online Journal, 2013)
The raw material is a very important thing in the production process, the quality of the raw material will determine the quality of finish produced. PT Masscom Graphy (Masscom) as a company engaged in the field of industrial printing Suara Merdeka ventures that already have the ISO on the selection process and evaluation of supplier should have attention to the selection process of suppliers to supply raw materials to be used. The importance of web ink raw material, making this research focuses on this raw materials. Grey based rough sets can be used to perform the selection of suppliers with the results of more than one supplier. Supplier 3 is the largest weighting on the supplier selection process supplier with four criteria (quality, cost, delivery, service) then followed by 2 and supplier supplier 1. On the other hand, the environmental criteria into the criteria important to taken into account, in accordance with the legislation of the Republic of Indonesia No. 5 of 1984, article 21. For this research will also be discussed the analysis sensitivity regarding the addition of environmental criteria. Supplier 3 is the largest supplier with a sensitivity analysis is performed after, followed by the supplier 6 and supplier 2.